Evaluation of transient elastography in assessing liver fibrosis in patients with autoimmune hepatitis. Issue 3 (March 2017) - Xu, Qinyu; Sheng, Li; Bao, Han; Chen, Xiaoyu; Guo, Canjie; Li, Hai; Ma, Xiong; Qiu, Dekai; Hua, Jing
Abstract: Background and Aim: Transient elastography (TE) can reliably stage liver fibrosis via liver stiffness measurement (LSM) in chronic liver disease. However, the accuracy of TE for assessment of liver fibrosis in patients with autoimmune hepatitis (AIH) is still limited. We evaluate TE in staging liver fibrosis in AIH patients and compare with other noninvasive diagnostic tools. Methods: A total of 100 patients with biopsy‐proven AIH were included. The correlation between LSM and fibrosis stage was analyzed using Spearman correlation test. The optimal cut‐off values of LSM were calculated for predicting individual fibrosis stages using receiver‐operating characteristic curve. The diagnostic accuracy of LSM for severe fibrosis was compared with those of serum biochemical scores. Results: Median LSM in AIH patients was higher than that of healthy controls (11.2 ± 8.2 kPa vs 4.3 ± 1.4 kPa, P < 0.01). LSM had significant correlation with fibrosis ( r = 0.752, P < 0.01) and increased progressively with increasing fibrosis stages in AIH patients. AUROC values of LSM for stages F ≥ 2, F ≥ 3, and F4 were 0.878 (95%CI: 0.789–0.967), 0.883 (0.820–0.946), and 0.914 (0.852–0.976), respectively. The optimal cut‐off values of LSM for fibrosis stages F ≥ 2, F ≥ 3, and F4 were 6.45, 8.75, and 12.50 kPa, respectively. LSM was superior to APRI score and FIB‐4 score in detecting severe fibrosis (F ≥ 3). Serum ALT levels had minor effect on LSM values. Conclusions: Transient elastography is an accurate and reliable noninvasive tool in assessing liver fibrosis in AIH. Hepatic inflammatory activity had no significant effect on LSM determination.